(untitled) (Bangladesh Journal of Psychology, 2024)
Bangladesh has experienced rapid economic growth and significant progress in expanding access to education over the past two decades. However, comprehensive programs that address the psychological and academic needs of children remain largely absent. The country faces a shortage of qualified professionals to manage students’ behavioral, emotional, social, and learning difficulties. School psychology is still in its nascent stage and has yet to be recognized as an independent discipline. This study aims to explore the perspectives of key stakeholders, including educators, psychologists, policymakers, parents, and students, on the importance of school psychology services. To gather insights, we conducted focus group discussions, interviews, and personal communications, alongside a review of relevant literature. The results show widespread agreement on the necessity of school psychology services to support mental health, address learning challenges, and promote overall students’ well-being. At the same time, significant challenges were identified, such as the scarcity of trained professionals, limited resources, lack of awareness, and cultural stigma surrounding mental health issues. The study concludes by emphasizing the urgent need for policy support and capacity-building initiatives to overcome these barriers and ensure the successful implementation of school psychology services in Bangladesh. This paper underscores the critical role of school psychologists in enhancing both academic and mental health outcomes for millions of children across the country. Bangladesh Journal of Psychology, Vol. 24, December 2024, pp. 23-32